A review on bornite (bio)leaching. (1st December 2021) - Hong, Maoxin; Liu, Shitong; Huang, Xiaotao; Yang, Baojun; Zhao, Chunxiao; Yu, Shichao; Liu, Yuling; Qiu, Guanzhou; Wang, Jun
Highlights: An overview on leaching and bioleaching behaviors of bornite is given. The intermediate products of bornite during dissolution are systematically discussed. Studies on co-leaching of bornite and other sulfide minerals are summarized. Possible inhibitory substances of hindering bornite (bio)leaching are discussed. Abstract: (Bio)Hydrometallurgy is a common technology in processing copper sulfide minerals. With the decline in ore grades and depletion of easily mined deposits, some complex ores with relatively small reserves need to be taken seriously. Bornite is one of the most important copper resources (following chalcopyrite and chalcocite) and the commonly associates in copper mines. However, less attention has been paid to bornite compared to chalcopyrite, and there are hardly any review papers on bornite (bio)leaching. The main purpose of this paper is to summarize the research on bornite (bio)hydrometallurgy. Leaching and bioleaching behavior of bornite are summarized, including co-leach with other sulfide minerals. The intermediate products and possible surface substances during bornite dissolution are discussed.